Metal hypersensitivity causing implant migration after anterior cruciate ligament reconstruction - Patra, Saroj Kumar; Unnava, Nikhil; Patra, Bishnu Prasad; Panda, Ritesh (International Surgery Journal, 2023)
A young female in her early twenties was diagnosed with Anterior cruciate ligament (ACL) deficiency. Operative intervention was advised with ACL reconstruction using a hamstring graft. The procedure was uneventful, and she was discharged on the second day. She was improving as per expectations. Six months later, the patient came with complaints of a discharging sinus which was located at the site of the tibial entry wound which healed with conservative therapy. However, she developed a similar discharge from the same site after one year of surgery. Radiographs showed migration of the implants away from the bone and towards the skin on the femoral and tibial side. The tibial implant was seen lying just beneath the skin through the discharging sinus. Finally, it was decided to remove the implants surgically. After implant removal, regular dressing was done, and the sinuses healed well without any further complications.